Scientific, professional and experiential validation of the model of preventive behaviours at work: protocol of a modified Delphi Study. Issue 9 (13th September 2020) - Lecours, Alexandra
Abstract : Introduction: To offer an in-depth understanding of preventive behaviours, those complex behaviours considered as levers to foster work prevention, recent theoretical and empirical studies permitted to develop the model of preventive behaviours at work. The next step is to validate the model with researchers, professionals and workers. This article aims to describe the study protocol that will be used to validate the model of preventive behaviours at work. Methods and analysis: This Delphi Study proposes seven systematic steps to conduct a scientifically rigorous validation study based on scientific and professional experts' opinion. A focus group to collect workers' opinion about the model has also been included in the protocol. Thirty experts (researchers and professionals) will be selected regarding their experience (eg, at least 5 years of experience) and expertise (eg, having published at least one article as the first author in the last 3 years) towards workers' health or organisational behaviours. Workers will be recruited to have a diversity in terms of age, gender and working conditions. Quantitative data will be analysed to calculate the percentage of experts' agreement on four content validity indicators (ie, comprehensiveness, representativeness, relevance and clarity). Qualitative data will be examined through a thematic analysis strategy. Ethics and dissemination: Approval of the research ethics board of the Centre intégré universitaire de santé et de services sociaux de la Capitale Nationale has been obtained. Findings will be shared with various stakeholders inclusive of researchers, professionals and workers. Findings will be disseminated in workshops, peer-reviewed journals and conferences.